Games with variable payoffs - Vilkas, E. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. И. Вилкас. Игры с изменяющимися выигрышами E. Vilkas. Lošimai su kintančiais išlošimais